Implementasi Standar Pengelolaan untuk Peningkatan Mutu Layanan Pembelajaran Pada SMAN 1 Nagrak Sukabumi dan SMAS Pasundan Bandung - Pratama, Panji; Yulianto, Hendra; Cepi Berlian, Ujang; Iriantara, Yosal (Institut KH Ahmad Sanusi (INKHAS) Sukabumi, 2021)
This study aims to test the quality of school services during the COVID-2019 pandemic, especially through an analysis of management standards that apply in schools. This study used a descriptive-qualitative method with a sample of two schools, namely SMAN 1 Nagrak Sukabumi Regency and SMA 3 Pasundan Bandung. In this study, the authors found that the quality of school services was not significantly affected by the COVID-19 pandemic when analyzed from the applicable management standards.